In vitro and in vivo characterization of CYP inhibition by 1‐aminobenzotriazole in rats. (May 2016) - Parrish, Karen E.; Mao, Jialin; Chen, Jacob; Jaochico, Allan; Ly, Justin; Ho, Quynh; Mukadam, Sophie; Wright, Matthew
Abstract: 1‐Aminobenzotriazole (ABT) is a non‐isoform specific, time‐dependent inhibitor of cytochrome P450 (CYP) enzymes used extensively in preclinical studies to determine the relative contribution of oxidative metabolism. Although ABT has been widely used, the extent and duration of its inhibitory effect is not well understood. The purpose of this study is to characterize ABT inhibition of CYP in rats at both the hepatic and intestinal levels. In vivo studies using midazolam (p.o. and i.v.), as a probe for CYP activity, demonstrated that CYP inhibition was not complete even at the highest dose (300 mg/kg). Additional in vivo studies demonstrated that even at 26 h following ABT administration, there was significant CYP inhibition remaining. In vitro studies, conducted in both rat liver microsomes and rat hepatocytes, confirm that ABT is a time‐dependent inhibitor of rat CYP orthologs. However, in rat liver microsomes, there was more than 15% CYP activity remaining following a 60 min preincubation at 2 mm ABT and 5–10% of CYP activity was remaining in rat hepatocytes suspended in rat plasma following a 60 min preincubation at 2 mm ABT. 1‐Aminobenzotriazole is a useful tool in elucidating the oxidative component of metabolism in preclinical species; however, conclusions made from the preclinical use of ABT should not operate under the assumption that CYP enzymatic activity is completely inhibited. Copyright © 2016 John Wiley & Sons, Ltd.